ANTIOXIDANT ACTIVITY OF A MIXTURE OF GLEDITSIA AND AILANTHUS FLOWERS (Scientific journal of the Fergana State University, 2026)
With the growing interest in natural antioxidants, special attention is given to the study of less explored medicinal plants and their combinations. In the present study, the antioxidant activity of alcoholic extracts of Ailanthus altissima and Gleditsia spp. flowers were evaluated when mixed in different ratios: 1:1, 3:1, and 1:3. To quantitatively assess the antiradical properties, the DPPH method was applied, based on spectrophotometric measurement of absorption at 517 nm. The values of ARF% (antiradical activity) and IC₅₀ (the volume of extract required to inhibit 50% of DPPH radicals) were determined. The results demonstrated that all studied mixtures exhibited pronounced antioxidant activity. The greatest effect was observed in the 1:1 mixture, for which the IC₅₀ was 207.07 μL, while the ARF% at a volume of 100 μL after 30 minutes reached 24.77%. These values are comparable to the results of well-known natural antioxidants.Thus, the synergistic combination of Ailanthus and Gleditsia flowers may serve as an effective source of natural antioxidants, with promising potential for the development of functional phytopreparations and dietary supplements.